NASIONALISASI PERUSAHAAN-PERUSAHAAN MILIK BELANDA ATAS TANAH KONSESI KESULTANAN DELI (Studi Awal Hilangnya Hak-hak atas Sumber Daya Alam Masyarakat Adat) - Saidin, OK. (Yustisia, 2015)
AbstractThe nationalization of Netherland plantation which became the national possession in 1958, regulated in the Act No. 86 of 1958 was the starting point of the loss of natural resource rights of the Malay indigenous people of Deli and also was the starting point of the conflict between the Malay indigenous people and the plantation party. When the plantation party which belong to the country (now PT Perkebunan Nusantara 2 (Persero)/National Plantation Company 2) was no longer continuing the right as received by the indigenous people from the time of Netherland plantation, third parties’ claims without any basis of rights (recht title) were occurred on the land. Nationalization has shown its mistake to nationalize the rights on the land of the society (not the possession of the foreign), whereas the meaning of nationalization is to nationalize what was not belong to the country. Was not the land belong to the Malay Indigenous people of Deli which is the society of Indonesia? Was not the Indigenous people stand as the possessor of this country? But the Act of Nationalization which clearly stated that what is nationalized was the Netherland’s companies which were listed in the Company Asset Listing such as Deli Maatschapij, Arrensburg Maatschapij and Deli Rubber Maatschapij. These objects of land were not listed as company asset that belong to foreign company (Netherland’s Company). What should have happened was the national company as the receiver post-nationalization was just continuing the vested rights, so that when the vested rights ended, the object of the vested rights (the land) must be given back to the original possessor (Deli Sultanate and Malay Indigenous people of Deli). AbstrakNasionalisasi perkebunan Belanda menjadi perkebunan milik negara pada tahun 1958, melalui Undang- undang No. 86 Tahun 1958 merupakan awal hilangnya hak-hak sumber daya alam Masyarakat Adat Deli sekaligus merupakan awal konflik masyarakat hukum adat Melayu dengan pihak perkebunan. Ketika pihak perkebunan negara tersebut (sekarang PT. Perkebunan Nusantara 2 (Persero)) tidak lagi meneruskan hak sebagaimana hak yang diterima masyarakat hukum adat dari pihak perkebunan Belanda dahulu, maka bermuculanlah klaim-klaim pihak ketiga yang tidak memiliki alas hak (recht title) di atas lahan tersebut. Nasionalisasi telah memperlihatkan kekeliruannya karena menasionalkan hak-hak atas tanah milik masyarakat (bukan milik asing), padahal pemaknaan nasionalisasi adalah menasionalkan yang bukan milik nasional. Bukankah tanah-tanah itu adalah milik Masyarakat Adat Deli yang notabene adalah rakyat Indonesia ? Bukankah masyarakat hukum adat itu adalah pemilik negeri ini ? Akan tetapi, undang-undang nasionalisasi yang secara tegas menyatakan bahwa yang dinasionalisasi adalah perusahaan Belanda dalam arti yang dinasionalisasi itu adalah asset yang terdaftar dalam Daftar Asset perusahaan semisal Deli Maatschapij, Arrensburg Maatschapij dan Deli Rubber Maatschapij. Obyek tanah tidak terdaftar sebagai asset perusahaan milik perusahaan asing (perusahaan Belanda). Seyogyanya perusahaan negara sebagai penerima asset pasca nasionalisasi hanyalah meneruskan hak-hak konsesi itu (vested rights), sehingga ketika hak konsesi itu berakhir, maka obyek konsesi itu (tanah) harus dikembalikan kepada pemiliknya (Kesultanan dan Masyarakat Adat Deli).